A cohort study on risk factors for preterm births in rural Gujarat - Poonam Trivedi; Deepak Saxena; Tapasvi Puwar; Shital Savaliya; Parthasarathi Ganguly (Wolters Kluwer Medknow Publications, 2018)
Background: Prematurity is one of the leading causes of neonatal and under-five mortalities globally and also in India. It is an important determinant of short- and long-term morbidities in infants and children. Unfortunately, risk factors of majority of preterm births (PTBs) remain unexplained which calls for appropriate action. There is a dearth of community-based research on PTB and its risk factors, especially in high burden countries like India. Objectives: The objective of the study was to explore different risk factors for PTB. Methods: A cohort of 1977 antenatal mothers was enrolled at household level by trained field investigators and was followed up in four districts of Gujarat, India, to document the outcome of pregnancy. Pretested and structured questionnaires were used to collect information. A hierarchical regression model was used to analyze the risk factors for PTB. Results: Proportion of PTB was 9% among the enrolled cohort. Risk factors which were found to be significant on applying the hierarchical model were periodontal disease, long sleep duration, and sex during any trimester. Conclusions: The study suggests an urgent need for strengthening of existing guidelines for effective, evidence-based, and culturally appropriate interventions for prevention of PTB. Maintenance of good oral hygiene should find a place in routine recommendations for pregnant women, and antenatal examinations should include screening for oral hygiene also.